The role of government and non-government organisations in the promotion of knowledge on Alzheimer’s disease in Poland and the European Union - Kaczyńska, Anna; Broczek, Katarzyna; Sienkiewicz, Zofia; Gotlib, Joanna (Polish Journal of Public Health, 2015)
The article presents the role of government and non-government organisations in promoting knowledge on Alzheimer’s disease in Poland and the European Union. There is a detailed analysis of the EU documents and non-government organisations in promoting knowledge on Alzheimer’s disease in Germany, France and Holland. There is a discussion on the National Alzheimer’s Plan on the basis of an example of introducing such a plan in Finland. Additionally, the rules of helping people suffering from Alzheimer’s disease and their attendants in Poland are presented.